The The Problems of Teachers' Readiness in Implementing New Curriculum; A Systematic Literature Review - Muhammad Helmi Labib; Ahmad Noor Ihsanuddin; Ikhrom (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Changes in the new curriculum policy turned out to raise various readiness problems among teachers, teachers are trained to implement the Merdeka Belajar Curriculum in their respective schools. For this reason, this research aims to conduct a literature review of the problems of teachers' readiness in implementing the new curriculum or the Merdeka Belajar Curriculum and find solutions. The method chosen in this research is SLR (Systematic Literature Review) method. In this research, 15 articles relevant to the Merdeka Belajar Curriculum and the problems faced by teachers in implementing it for the period 2022-2023 are reviewed with a focus on problems, teacher readiness and new curriculum implementation. The articles used in this study were obtained from Sinta Journal, and Publish or Perish.The results of this study show that firstly, most teachers faced challenges in understanding the concepts and teaching strategies promoted by the new curriculum. This indicates the need for increased training and debriefing of teachers to enable them to play their role as learning facilitators in the spirit of this curriculum. Second, limited facilities and infrastructure, both in terms of funds and teaching materials, are a serious obstacle to the implementation of this curriculum. Therefore, there is a need for further support from the government and related parties to ensure the availability of adequate infrastructure.